2008
DOI: 10.1364/josaa.25.000911
|View full text |Cite
|
Sign up to set email alerts
|

Image fidelity for single-layer and multi-layer silver superlenses

Abstract: In response to increasing interest in the area of subdiffraction-limited near-field imaging, the performance of several different realizable and theoretical superresolving silver-based lenses is simulated for a variety of different input object profiles. A computationally-efficient T-matrix technique is used to model the lenses, which consist of layers of silver with total width of 40 nm sandwiched between layers of polymethyl methacrylate and silicon dioxide. The lenses are exposed to nonperiodic bright- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 13 publications
1
39
0
Order By: Relevance
“…In this regime, incorporation of additional layers improves transmission characteristics. However, these structures show large impedance mismatch, and compared to a single-layer superlens they do not always offer better resolving power [9]. Using these structures, subwavelength resolution can also be achieved at frequencies different from the plasmon resonances of the individual layers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regime, incorporation of additional layers improves transmission characteristics. However, these structures show large impedance mismatch, and compared to a single-layer superlens they do not always offer better resolving power [9]. Using these structures, subwavelength resolution can also be achieved at frequencies different from the plasmon resonances of the individual layers.…”
Section: Introductionmentioning
confidence: 99%
“…While this analysis reveals a lens's transmission coefficients over a range of spatial frequencies, it does not provide a measure of image-reconstruction capability, which is required for practical imaging [9]. Due to near-field operation, superlens performance is sensitive to the coupling between object and lens, but these interactions have not attracted considerable attention in the literature [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pendry found that if the refractive index of a layer is exactly minus one, it can act as a perfect lens which has the ability to recover, in principle, all the subwavelength information of an object in the image domain [9]. This pioneering work has encouraged immense amounts of research to theoretically design [10][11][12][13][14][15][16][17][18][19][20][21][22][23] or experimentally fabricate [24][25][26][27][28][29][30] a super resolution imaging system. Although many well known experiments have made progress in trying to realize a superlens and some encouraging results have been reported, the main obstacle for the superlens to be applied to real application is that fabrication issues remain a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many approaches of imaging beyond the diffraction limit with superlens have been reported [13][14][15][16][17][18]. The performance limit of the metallic superlens was associated with the intrinsic losses of metal.…”
Section: Introductionmentioning
confidence: 99%